The conditions and factors of negative consequences of reconstruction -thermal modernization of buildings - Sokolenko, Valerii; Holodnov, Oleksandr; Sokolenko, Konstyantin; Filatiev, Myhailo (Academic journal Industrial Machine Building Civil Engineering, 2020)
The negative consequences analysis of public buildings thermal modernization for cases of work stoppage has been carried out. The negative consequences arise for the environment and the facility residents. Organizational and construction mistakes have a long complex character and cannot be corrected. The problem from the technical side turns into an administrative process. The task is to propose organizational and technological measures that would make such cases impossible in the future. It is proposed to carry out work by an integrated method, to complete facade work within a certain section of the wall. Advance financing should be tightly linked to the project sequence of work